â€Satlogi Santriâ€ sebagai Sistem Nilai dan Falsafah Hidup Pesantren Zainul Hasan Genggong Probolinggo - Herwati Herwati (STAI Syaichona Moh. Cholil Bangkalan, 2020)
Moral decadence is a common thing among Islamic boarding schools in the archipelago. Violating ethical values â€‹â€‹which results in the degeneration of santri morals, obedience to kiai being ignored, western cultural civilization that promotes individual freedom has become a common phenomenon at Pesantren Zainul Hasan Genggong. The aims of this research is reveal the meaning and implementation of the satlogy santri in the Zainul Hasan Genggong Islamic boarding school. The methodology of this research is descriptive qualitative with three data collection instruments, namely interviews, observation and documentation. The results of this study are the satlogi santri which are the philosophical values of the Zainul Hasan Genggong Islamic Boarding School which adhere to six principles, namely Polite Santun, Ajeg / Istiqamah, Advice, Taqwallah, Ridlallah, and Ikhlas Lilahi Ta'ala) with the aim that students and alumni besides mastering science, also in order to have the identity of students who are able to practice knowledge and knowledge that is practical in everyday life so that they can become role models for the ummah to give their best in social life.